2009
DOI: 10.1021/es900471g
|View full text |Cite
|
Sign up to set email alerts
|

Sea Ice-associated Diet Change Increases the Levels of Chlorinated and Brominated Contaminants in Polar Bears

Abstract: Two global environmental issues, climate change and contamination by persistent organic pollutants, represent major concerns for arctic ecosystems. Yet, it is unclear how these two stressors interact in the Arctic. For instance, the influence of climate-associated changes in food web structure on exposure to pollutants within arctic ecosystems is presently unknown. Here, we report on recent changes in feeding ecology (1991-2007) in polar bears (Ursus maritimus) from the western Hudson Bay subpopulation that ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
105
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 122 publications
(110 citation statements)
references
References 65 publications
5
105
0
Order By: Relevance
“…It is therefore possible that long-range annual migrations mitigated by sea ice habitat loss will result in increased uptake and accumulation of POPs due to the increased feeding demands needed for longer migrations. In some regions, decline of sea ice extension has resulted in changes in the presence of seal species that polar bears depredate, and this has been shown to cause increased bioaccumulation of certain POPs (Thiemann et al, 2008;McKinney et al, 2009McKinney et al, , 2013. Dietary shift toward feeding on plants, berries and caribou (Rangifer tarandus) and seabird eggs, respectively (Ramsay and Hobson, 1991;Gormezano and Rockwell, 2013a,b;Iles et al, 2013;Iverson et al, 2014), will most likely decrease and increase, respectively, the dietary uptake of POPs.…”
Section: Combined Effects On Energetic Processesmentioning
confidence: 99%
“…It is therefore possible that long-range annual migrations mitigated by sea ice habitat loss will result in increased uptake and accumulation of POPs due to the increased feeding demands needed for longer migrations. In some regions, decline of sea ice extension has resulted in changes in the presence of seal species that polar bears depredate, and this has been shown to cause increased bioaccumulation of certain POPs (Thiemann et al, 2008;McKinney et al, 2009McKinney et al, , 2013. Dietary shift toward feeding on plants, berries and caribou (Rangifer tarandus) and seabird eggs, respectively (Ramsay and Hobson, 1991;Gormezano and Rockwell, 2013a,b;Iles et al, 2013;Iverson et al, 2014), will most likely decrease and increase, respectively, the dietary uptake of POPs.…”
Section: Combined Effects On Energetic Processesmentioning
confidence: 99%
“…The majority of these studies are conducted in Nunavut and reflect research effort in a small number of settlements (Igloolik, Arctic Bay, Cape Dorset, Clyde River) and by a cluster of researchers from a geography background. Health and well-being is examined in 25 % (n = 29) of studies, mostly examining food systems and safety of land-based activities, with recent publications examining the fate of contaminants in light of climate change (McKinney et al 2009;Gantner et al 2010;Kuzyk et al 2010;Macdonald and Loseto 2010). Mental health and vector-and water-borne diseases have received limited attention.…”
Section: The Majority Of Studies Focus On Subsistence Hunting Fishinmentioning
confidence: 99%
“…Andersen et al (2001) suggested that the variation observed in their study is due to polar bears facing different PCB exposure between the regions, something that can be caused by heavier pollution in some areas compared to others, but also by differences in the food webs polar bears rely on. Variation in levels and patterns of various pollutants found in polar bear tissue can be explained by regional prey differences or changes in the diet, as was demonstrated for Hudson Bay polar bears (Mckinney et al 2009). Satellite tracking of individuals has shown that polar bears in the Kara and Laptev seas spend considerable amounts of time in multi-year ice .…”
Section: Pcb Contaminationmentioning
confidence: 86%